Creation Music Lawat Sagara | Tabuh Kreasi Lawat Sagara - I Kadek Yogi Aditya (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
Lawat Sagara is a musical work inspired by the reflection of marine life. The ocean with stunning views creates a peaceful mood. The flora and fauna include fish, particles, and the high biodiversity in the coral reef area with various beautiful colors. Human behavior often ignores issues regarding environmental sustainability. Awareness of harmonizing human relations with the environment must be promoted more widely. This awareness in Bali is known as the concept of tri hita karana. Tri means three, hita means balance or prosperity, and karana implies cause. Tri hita karana can be interpreted as three causes of prosperity in life. Apart from being related to aesthetics, this work aims to convey the importance of maintaining environmental balance in the concept of tri hita karana. With this concept, it is an image or reflection of the ocean, which is also the main element of this work. In creating the work, one barungan gamelan selonding is used which is combined with several Balinese instruments, such as the kerumpungan drum, cedugan drum, kecek ricik, kajar trenteng, flute and pencon gong. The aim is to combine the barungan selonding instruments with gamelan instruments to enrich the rhythm and accentuation in the work. The use of selonding gamelan has characteristics that can evoke the atmosphere in the production of Lawat Sagara. The stages or methods in the work of Lawat Sagara use the Panca Sthiti Nawi Sani creation method: inspiration (ngawirasa), exploration (ngewacak), conception (ngaplan), execution (ngawangun) and ngebah (maedeng).